An experimental study of adiabatic two-phase gas-liquid flow in helical micro-tube - Adirek Suriyawong; Kritsada Pratuyai; Somchai Wongwises; Sira Saisorn (AIP conference proceedings, 2021)
The development of two-phase flow patterns in helical micro-tube was experimentally investigated. The adiabatic gas-liquid two-phase flow regime maps were presented based on a 0.87 mm inner diameter tube which was helical glass channel. Working fluid in the helically coiled tube was air-water mixture flowing in vertical upward direction. The diameter of the helical coil and the relevant pitch were, respectively, 50 mm and 20 mm. Flow visualization was carried out at different positions along the micro-tube length in order to examine the significance of the centrifugal force existing in addition to the conventional force vectors. In this work, slug flow, churn flow, throat-annular flow, and annular flow were observed and compared to the existing flow transition boundaries developed from micro-channel configurations.
Keywords: Heat Transfer and Boiling Studies; Heat Transfer and Optimization; Fluid Dynamics and Heat Transfer